Analysis Based on Clinical Data and Imaging - Factors Affecting the Prognosis of Patients with Optic Neuritis - Wen, Yanbin; Guo, Nianbo; Luan, Lijuan (Alternative therapies in health and medicine, 2024)
To analyze the risk factors that affect the prognosis of patients with optic neuritis through imaging examinations and clinical data analysis. 130 patients with optic neuritis admitted to our hospital from February 2018 to February 2022 were selected as the study subjects. They were divided into a poor prognosis group (n = 52) and a good prognosis group (n = 78) based on their prognosis. Imaging examination and clinical data analysis, along with the assessment of the predictive value of statistically significant continuous variables using ROC experiments and risk factors using logistic regression were performed. The results showed that there was no statistically significant difference in general data such as gender and BMI between the two groups (P > .05). Compared with the group with good prognosis, the group with poor prognosis had higher age (34.47 ± 1.58 years vs 35.81 ± 2.60 years), onset to visit interval (1.81 ± 0.40 weeks vs 2.50 ± 0.64 weeks), VCAM-1 (608.70 ± 42.80 ng/mL vs 625.58 ± 35.62 ng/mL), recurrence rate (48.72% vs 69.23%), optic nerve atrophy rate (3.85% vs 15.38%), eye rotation pain rate (28.21% vs 30.77%), and MRI long T2 signal rate (21.79% vs 40.38%). The proportion of MRI T1 enhanced signals was relatively high (17.95% vs 34.62%) (P < .05). Age, the interval between onset and visit time, and AUC of VCAM-1 were 0.657, 0.785, and 0.621, and the optimal cutoff values were 35 years old, 2 weeks old, and 620.29 ng/mL; 95% CI was (0.596 0.738), (0.704 0.852), and (0.532 0.704), P < .05. Age (>35 years old), recurrence (yes), interval between onset and visit (>2 weeks), MRI long T2 signal (yes), and MRI T1 enhanced signal (yes) are all risk factors that affect the prognosis of patients with optic neuritis. Clinical attention should be paid to high-risk populations.